Una arqueología del nation branding : las exposiciones binacionales del Londres eduardiano - Jorge Villaverde (Amnis)
Several bi-national exhibitions staged in the Edwardian London became the first contemporary campaigns of public diplomacy. The emergence of exhibitions as a medium, the rise of mass consumption and mass media as well as the increased differentiation of leisure practices produced an environment where some developing countries used the setup of bi-national exhibitions to sell their country in the capital of the leading world power. The governments of these countries sought to renegotiate their national image abroad by displaying both their cultural idiosyncrasy and economic development in order to find foreign investments, forge political alliances and improve their country’s outside perception.